2019
DOI: 10.17269/s41997-019-00204-5
|View full text |Cite
|
Sign up to set email alerts
|

Income-based inequities in access to mental health services in Canada

Abstract: Objectives While mental health services provided by general practitioners and psychiatrists can be billed to public health insurance programs in Canada, services provided by psychologists, social workers and other non-physician providers cannot. This study assesses the extent to which access to mental health services varies by income after first taking into account the higher concentration of mental health needs at lower income levels. Method Data from the Canadian Community Health Survey 2013-2014 are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Medical staff with low income, medium-low income, and very low income levels were all susceptible to anxiety, staff with a mediumlow income level were also vulnerable to depression and sleep disorders. It has been reported that income level is related to mental health both in developed countries such as Canada (Bartram, 2019) and developing countries such as Turkey (Kose, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Medical staff with low income, medium-low income, and very low income levels were all susceptible to anxiety, staff with a mediumlow income level were also vulnerable to depression and sleep disorders. It has been reported that income level is related to mental health both in developed countries such as Canada (Bartram, 2019) and developing countries such as Turkey (Kose, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the number of immigrants between the two regions could explain why immigrants in the Fredericton area fared much better than the immigrants in the Madawaska region, as social psychology theories tend to agree that larger ingroups increase group identification and, in turn, the well-being of its members ( 42 ). Income-based inequities in access to mental health services may also be a root cause ( 43 ). Looking beyond the OLMCs, some general tendencies emerged for all New Brunswick youth, regardless of social group status.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,16 This two-tier system leaves the lowest income Canadians facing the greatest barriers in accessing MHSUH services as they are least likely to have access to benefits or to be able to afford to pay out-of-pocket. 17 This two-tier system also means that many providers in the MHSUH workforce work in the private sector and are paid through some combination of direct out-of-pocket payments, employment-based benefit programs, or by private employers such as bed-based addiction treatment centres.…”
Section: Long-standing Exclusion Of the Mental Health And Substance U...mentioning
confidence: 99%